Supramolecular Structure and Function 10 - Brnjas-Kraljević, Jasminka; Pifat-Mrzljak, Greta (Springer Netherlands : Imprint: Springer, 2011)
The book is based on lectures presented on the International Summer School on Biophysics held in Croatia in September 2009. The advantage of the School is that it provides advanced training in very broad scope of areas related to biophysics contrary to other similar schools or workshops that are centered mainly on one topic or technique. In this volume, tenth in the row, the papers in the field of biophysics are presented. The topics are biological phenomena from single protein to macromolecular aggregations structure by using variant physical methods (NMR, EPR, FTIR, Mass Spectrometry, etc.). The interrelationship of supramolecular structures and their functions is enlightened by applications of principals of these physical methods in the biophysical and molecular biology context.